efek Residu Pengapuran dan Pupuk Kandang Terhadap basa-basa dapat ditukarkan pada ultisol dan Hasil Kedelai - Yunus Yunus (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
This research was aimed to study liming residual effect and manure to exchangeable bases at Ultisols and soybean yield. The research was conducted from March until July 2005 in the Experimental Station Faculty of Agriculture, University of Jambi. The experiment was in factorial design which was arranged within randomized block design (RBD). The treatment consisted 2 factors, the first was manure residue (b) : b0 = 0 ton/ha, b1 = 10 ton ton/ha, b2 = 20 ton/ha, the second factor was lime residue (c) : c0 = 0,0 x exch-Al, c1 = 1,0 x exch-Al, c2 = 2,0 x exch-Al. The result indicated that there was an interaction between manure and lime residue to exch-Ca and -Al, base saturation, and Al saturation. Meanwhile, prominent factor from manure residue could improve soybean yield. Key Words: Al-saturation, Soybean yield, liming